Peculiarities of calculating the geometric parameters of a diamond cutter for the formation of ring Fresnel lenses - Зенін, В. М.; Антонов, Є. Є. (Інститут проблем реєстрації інформації НАН України, 2024)
An algorithm has been developed for calculating the angles of mutual location and inclination of the cutting part of the diamond tool under the production of microprism ring plastic lenses and the corresponding metal matrices by the method of blade microcutting. When using a diamond tool and special precision equipment, this method allows one to obtain high accuracy of the geometric parameters of the microstructure of the lens and high purity of the processed working refracting surfaces, which in turn leads to the high quality of the image in the lens focus. Working formulas are given for calculating the angles of inclination of the cutting face of the cutter relative to the front face and to the central axis of the cutter depending on the angle at its apex. The working refracting surface of the lens groove is inclined at certain angle to the plane of the lens, the second non-working groove surface is perpendicular to this plane. These specified surfaces are formed with a specially made diamond cutter, which is a metal rod with a fixed diamond. The front working face of the diamond is located at the necessary angle to the central axis of the cutter. This angle is usually set to ~24 degrees, based on the technological considerations. The angle at the tip of the cutter should be smaller than the additional angle of the lens groove with the minimum value of microprism refractive angle. During the microcutting process these cutter's angles should be settled so, that in the process of turning the lens it is not allowed to touch the rear parts of the cutter to the vertical non-working surfaces of the groove. If this requirement is not met, it is necessary to correct the geometry of the cutter. A calculation algorithm is proposed and the range of critical parameters of the lens is defined, under which the above damage of the forming refractive surfaces of the lens cannot be fixed during the lenses and matrixes manufacture. Tabl.: 2. Fig.: 6. Refs: 5 titles.